Islamic perspective of quality administration - Shuriye, Abdi Omar (2009)
Conceptually quality is an acquired trait, a sort of accomplishment, and eminent character. The concept itself has no religion, so to speak; any one regardless of his or her religious proclivity could do quality job or acquire quality status or achieve superior ranking or perform with excellence. In other words, it matters less whether you are Hindu, Christian, Buddhist or a Muslim in achieving quality or doing quality job. However, religious teachings are instrumental in shaping and guiding mankind to achieve and perform better provided that man adheres to these teachings and drives the right message related to his or her work. The aim of this paper is to illumine Islamic perspective of quality administration. Quality, in its conventional sense, is related to customer’s perspective, the work of professionals such as engineers, doctors and lawyers; nonetheless all those who provide services including the administrators are by virtue of their profession expected to achieve and produce quality services. As an operational mechanism quality remains multidimensional and comprehensive in scope. On balance, one may summit that quality revolves around performance, reliability, durability, serviceability, and Aesthetics.